A new approach to analyzing wellbore pressure dynamically in well-killing - Liu, Pu; Wang, Zhiping; Wang, ChenLong; Tang, Zhengqiang; Yu, Hao; Liu, Huixin; Li, Kaixuan (Frontiers in Earth Science, 2023)
Casing pressure during well-killing is both an unknown variable that must be addressed and a time-dependent function.Therefore, the calculation of the dynamic reaction of wellbore pressure during well-killing is a dynamic indeterminate boundary problem. Due to the intricacy of the analytical solution technique, finding an analytical solution for the dynamic issue of uncertain boundaries is nearly impossible. Current numerical simulation software is only capable of resolving problems with defined bounds (such as flow or pressure) and is incapable of continuously calculating the wellbore pressure, which varies dynamically with well-killing time. Developing a dynamic reaction computation method for wellbore pressure during well-killing can solve this issue. Based on the mathematical model and definite solution conditions of the wellbore pressure dynamic response under well-killing conditions, this paper applies the finite difference principle and constructs the calculation method of choke and kill wellbore pressure dynamic response through reasonable mesh division of wellbore and gradual iteration of the calculation process. The resultsdemonstrate that the maximum wellhead casing pressure value and the time node of peak value are both highly congruent with the measured data, indicating the method's high reliability and highlighting its significance for the progress of oil and gas well control safety.